Imaging Profile of the Ear in Hearing Loss Patients in Hospital Universiti Sains Malaysia: 5 year Cross Sectional Analysis at a Tertiary Otologic Centre - Japar, Rohaizam; Sidek, Dinsuhaimi; Sheikh Ab. Hamid, Suzina; Yunus, Rohaizan (JPMS, Pakistan, 2017)
BACKGROUND: Hearing impairment is a major disability. The otologic assessment together with high-resolution CT images is an important step to obtain precise diagnostic profile of ear malformations. This study was conducted to obtain the detailed anatomy and objective assessment of the ear in patients presenting with hearing loss in a tertiary care otologic center using high-resolution CT scan. METHODS: A cross-sectional study of 55 patients with hearing loss who had undergone high-resolution CT scans at Hospital Universiti Sains Malaysia from 1st January 2008 until 31st May 2014. Patients with temporal bone fractures, malignancy, post-operative ear and cholesteatoma were excluded. RESULTS: Nine patients noted to have external ear anomaly on right ear and 7 patients on left ear. Middle ear abnormality in both ears was seen in 2 patients. Patients noted to have cochlear anomaly on the right ear (R) were 8 and left ear (L) were 4. Measurements of vestibular aqueduct diameter were 0.08 ± 0.09 cm (R) and 0.06 ± 0.04 cm (L), lateral semicircular canal diameter 0.10 ± 0.03 cm (R) and 0.10 ± 0.02 cm (L), vestibule diameter 0.30 ± 0.06 cm (R) and 0.31 ± 0.05 cm (L), bone width between the lateral vestibular wall and the inner wall of the lateral semicircular canal diameter 0.35 ± 0.07 cm (R) and (L) and internal acoustic meatus diameter 0.40 ± 0.08 cm (R) and 0.41 ± 0.08 cm (L). One patient had cochlear aplasia and common cavity deformity, 2 patients had lateral semicircular dehiscence and internal acoustic meatus stenosis, 4 patients had cochlear ossification and 5 patients were noted to have enlarged vestibular aqueduct. CONCLUSION: High-resolution CT scan image is a good single imaging modality to obtain an objective measurement of the ear as well as to detect subtle or underestimated ear anomalies